Membangun Konsep Pendidikan Multikultural Untuk Indonesia - Munawir Haris (Al-Riwayah : Jurnal Kependidikan, 2017)
The reality of the diversity of the Indonesian people for this in the name of national stability is often the reason in this era. Today, discussing the concept of multicultural education in the public life of multiculturalism is very risky because nations mental is not ready yet to accept it. But these circumstances have to be blasted and blasted peacefully continue to seek and find the best solution to the nation. The paradigm of multicultural education includes the subjects of injustice, poverty, oppression and backwardness of minorities in various areas of social, cultural, economic, and errors in understanding other religions. Multicultural education should be directed so that all nations can enter into an entity called multicultural education institution, regardless of religion, poor, rich, gentry, students, and so on. Perhaps only with the well multicultural education will be able to be a solution for the nation of Indonesia. Promoting the concept of multicultural education is as part of efforts to reduce the potential horizontal and vertical national conflict. Multiculturalism is a risk that needs to be taken in developing the nation of Indonesia. This paper attempts to describe phenomena and urgency of multicultural education in the nation life.